The Trends for the Coefficient Combined Ratio in the Selected Insurance Companies for Property and Life Insurance Products in Poland in the Years 2002–2010 - Wieteska, Stanisław (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
An important part of the insurance is to study the economic efficiency and their performance. Economic efficiency in the insurance is to operate in such a way in order not to loose on insurance products. One of the indicators that say about the economic condition of the insurance is, combined ratio. In this work we present the size of coefficient combined ratio in insurance industry for the life and property insurance. We also indicate the behavior of this coefficient in communications insurance.